2023
DOI: 10.3390/nu15214695
|View full text |Cite
|
Sign up to set email alerts
|

See Me, Hear Me, Know Me: Perspectives on Diet and Physical Activity Influences among Teens Living in Rural Texas Communities

Debbe Thompson,
Julie Miranda,
Chishinga Callender
et al.

Abstract: Teens in rural communities are at greater risk of obesity than teens in urban areas. Diet and physical activity influence obesity risk. Understanding their perspectives is an important step in intervention design. This qualitative investigation explored teen perspectives on how living in a rural community influenced their diet and physical activity choices. Forty parent–teen pairs were recruited. Data collection included surveys and telephone interviews. This paper reports teen perspectives identified in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This suggests that the urban–rural difference in food insecurity may be due to other factors, such as access to healthy food and transportation. In fact, a recent study found that most families of teenagers drove a distance of 10 miles or less to grocery shop at least once a week [ 47 ]. Nonetheless, this disparity warrants the need for targeted interventions to address food security challenges, particularly in urban environments.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the urban–rural difference in food insecurity may be due to other factors, such as access to healthy food and transportation. In fact, a recent study found that most families of teenagers drove a distance of 10 miles or less to grocery shop at least once a week [ 47 ]. Nonetheless, this disparity warrants the need for targeted interventions to address food security challenges, particularly in urban environments.…”
Section: Discussionmentioning
confidence: 99%